Investigating the interplay of the hydrometeorological and seasonal forest vegetation role in regulating the nitrate flushing in a small torrential catchment - Lebar, K.; Kastelec, D.; Rusjan, S. (The Science of the total environment, 2023)
Forest vegetation is a very topical research subject as part of nature-based solutions for flood protection, soil erosion, water quality improvement, etc. However, limited capabilities of such measures are rarely investigated. Therefore, in this paper, study on the interplay of the hydrometeorological and seasonal forest vegetation role in regulating the nitrate‑nitrogen (NO3-N) flushing from a forested, torrential catchment is presented. For the 43 identified rainfall events it was found that there are no statistically significant seasonal differences in NO3-N concentrations; however, during baseflow conditions such differences were noted. The rainfall events were described by 17 hydro-meteorological and vegetation variables to investigate similarities between the events from the NO3-N export point of view using clustering methods. Additionally, the relationship between explanatory and dependent variables, i.e. NO3-N concentration and export variables, was modelled. In the models, the first four principal components were used as explanatory variables after the reduction of the initial number of variables. It was found that phenological phases as indicators of the forest vegetation seasonal activity are generally not able to considerably influence the NO3-N concentration and flushing dynamics. The results indicate that during baseflow conditions, the influence of the forest vegetation in the torrential catchment becomes predominant. During rainfall events, the role of vegetation is blurred and might be generally considered as insignificant. The characteristics of rainfall events apparently exceed the limits of a forest's ability to control NO3-N flushing. Given the pronounced impact of rainfall intensity on NO3-N flushing, the challenge for the future will be to mitigate the potential negative effects of climate change related impacts, especially through measures able to reduce the intensity of rainfall-runoff formation. The seasonal role of vegetation in diminishing the intensity of nutrient flushing in natural torrential catchments might be relatively constrained and probably also overwhelmed by the hydrometeorological conditions. [Display omitted] •Rainfall event vs. forest vegetation role in NO3-N flushing•Multivariate statistical analyses of 17 variables defined on high-frequency data•Predominance of forest vegetation role during baseflow conditions•Identification of rainfall event controls of NO3-N flushing